EVENT CANDIPURO CULTURE FESTIVAL : STRATEGI PROMOSI PARIWISATA BERBASIS BUDAYA - Nawangsih Nawangsih (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
The unique and interesting tourism potential and local wisdom that the region has had so far is still not being promoted. The Candipuro Culture Festival event can become an opportunity and explore the value of cultural tourism in a region to be promoted as a potential tourist destination for tourists. The purpose of the study was to find out the tourism promotion strategies carried out in promoting and cultural attractions displayed in the Candipuro Culture Festival Event The study used a qualitative descriptive method. collecting data technique are interviews, observation and documentation. step of data analysis activities: data collection, data reduction, data presentation and conclusion drawing. The results that the promotion strategy used in the Candipuro Culture Festival Event was conducted using online and offline media to increase the number of tourist visits. Cultural attractions displayed at the Culture-based Candipuro Culture Festival Event, namely in the form of traditional arts and local wisdom of local residents, but there are cultural elements whose meaning has begun to shift, so more attention is needed. The importance of cultural preservation from generation to generation so as not to lose meaning.